'Goal-directed extracorporeal circulation: transferring the knowledge and experience from daily cardiac surgery to extracorporeal membrane oxygenation'. (April 2023) - Condello, Ignazio; Santarpino, Giuseppe; Nasso, Giuseppe; Moscarelli, Marco; Speziale, Giuseppe; Lorusso, Roberto
Metabolism management plays an essential role in extracorporeal technologies. There are different metabolic management devices integrated to extracorporeal devices; the most commonly used and accepted metabolic target in adult patients is indexed oxygen delivery (280 mL/min/m 2 ) and cardiac index (2.4 L/min/m 2 ), which can be managed independently or according to other metabolic parameters. Extracorporeal membrane oxygenation (ECMO) is a temporary form of life support providing a prolonged biventricular circulatory and pulmonary support for patients experiencing both pulmonary and cardiac failure unresponsive to conventional therapy. The goal-directed perfusion initiative during cardiopulmonary bypass (CPB) reduced the incidence of acute kidney injury after cardiac surgery. On the basis of the available literature, the identified goals to achieve during CPB include maintenance of oxygen delivery > 300 mL O2 /min/m 2 and reduction in vasopressor use. ECMO and CPB are conceptually similar but differ in many aspects and finality; in particular, they differ in the scientific evidence for metabolic management nadirs. As for CPB, predictive target parameters have been found and consolidated, particularly in terms of acute renal injury and the prevention of anaerobic metabolism, while for ECMO management, a blurred path remains. In this context, we review the strategies for optimal goal-directed therapy during CPB and ECMO, trying to transfer the knowledge and experience from daily cardiac surgery to veno-arterial ECMO.